Design of TOEFL English Exam Simulation Application Model for Trisila Dharma Polytechnic Student Environment - Risda Purwanti; Rismayanti Putri (Journal of Multimedia Trend and Technology, 2023)
The Language Training Unit is a forum for an institution to manage language-related activities. In improving the quality of an educational institution, the need for performance is very much considered. Language Training Unit which aims to improve the quality of students in terms of language understanding. Multilingual skills in the Trisila Dharma Polytechnic environment need to be developed, especially for students and all teaching staff in the environment. The need for TOEFL implementation is one of the considerations of Trisila Dharma Polytechnic, where the function and benefits of TOEFL have become one of the obligations of most universities in Indonesia. This language skill can also be used as a companion to a diploma in accordance with Indonesian regulations, namely through the Ministry of Education and Culture Institution no. 81 of 2014. This background underlies the design of the TOEFL test simulation application at the Trisila Dharma Polytechnic Language UPT. The author used observation, interview, questionnaire, and literature study techniques to collect data. The system development method used is the waterfall method. This application can be used to make TOEFL implementation easier, especially the type of assessment that uses website-based information technology.